PENGEMBANGAN MEDIA PEMBELAJARAN E-BOOKLET INTERAKTIF BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR MATERI BANGUN RUANG - Laelatul Fitri, Fajar; Sutiah; Abdussakir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop and test improvements in student learning outcomes using interactive e-Booklet learning media based on augmented reality (AR) on class V classroom materials at SDI Daarul Fikri Malang. The research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of needs analysis, design, development, implementation and evaluation. Research instruments include interviews, observation, expert validation, learning outcomes tests, and student response questionnaires. The research results showed that the learning media developed received an average expert validation of 96% (category "Very Valid") and a positive response from students of 91.8%. The N-Gain test shows an increase in student learning outcomes with an average score of 0.61 ("Medium" category). This learning media is considered effective and innovative in increasing students' understanding of spatial building material.